2005
DOI: 10.1038/sj.onc.1208682
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor WARTS activates the Omi / HtrA2-dependent pathway of cell death

Abstract: Drosophila tumor suppressor WARTS (Wts) is an evolutionally conserved serine/threonine kinase and participates in a signaling complex that regulates both proliferation and apoptosis to ensure the proper size and shape of the fly. Human counterparts of this complex have been found to be frequently downregulated or mutated in cancers. WARTS, a human homolog of Wts, is also known as tumor suppressor and mitotic regulator, but its molecular implications in tumorigenesis are still obscure. Here, we show that WARTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 52 publications
0
45
1
Order By: Relevance
“…We found that WTS can promote the protease activity of Omi to induce cell death (Kuninaka et al, 2005). However, recent reports using Omi protease mutant or knockout mice indicate that loss of protein or protease activity of Omi sensitizes some types of cell death stimuli, which contradicts the previous findings.…”
Section: Proteolysis Of Warts By Omi Protease S Kuninaka Et Alcontrasting
confidence: 56%
See 4 more Smart Citations
“…We found that WTS can promote the protease activity of Omi to induce cell death (Kuninaka et al, 2005). However, recent reports using Omi protease mutant or knockout mice indicate that loss of protein or protease activity of Omi sensitizes some types of cell death stimuli, which contradicts the previous findings.…”
Section: Proteolysis Of Warts By Omi Protease S Kuninaka Et Alcontrasting
confidence: 56%
“…Therefore, binding of these two molecules is important for signal transduction. When the C-terminal three amino acids (Val-Tyr-Val) of WTS are removed it is prevented from associating with Omi (Kuninaka et al, 2005). As LATS2 (LTS2), another member of the class of mammalian WTS/ LATS1 kinase, has the same three C-terminal amino acids as WTS, it is possible that LTS2 also contributes to the Omi-mediated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations